Angle-Resolved Plasmonic Properties of Single Gold Nanorod Dimers - Wu, Jian; Lu, Xuxing; Zhu, Qiannan; Zhao, Junwei; Shen, Qishun; Zhan, Li; Ni, Weihai (Nano-Micro Letters, 2014)
Through wet-chemical assembly methods, gold nanorods were placed close to each other and formed a dimer with a gap distance 1 nm, and hence degenerated plasmonic dipole modes of individual nanorods coupled together to produce hybridized bonding and antibonding resonance modes. Previous studies using a condenser for illumination result in averaged signals over all excitation angles. By exciting an individual dimer obliquely at different angles, we demonstrate that these two new resonance modes are highly tunable and sensitive to the angle between the excitation polarization and the dimer orientation, which follows cos2φ dependence. Moreover, for dimer structures with various structure angles, the resonance wavelengths as well as the refractive index sensitivities were found independent of the structure angle. Calculated angle-resolved plasmonic properties are in good agreement with the measurements. The assembled nanostructures investigated here are important for fundamental researches as well as potential applications when they are used as building blocks in plasmon-based optical and optoelectronic devices.